Protective Effects of the Ketogenic Diet on Cognitive Impairment Induced by Status Epilepticus in Rats: Modulation of Neuroinflammation Through the NF‐κB Signaling Pathway - Wandi Wang; Lingman Wang; Chunxue Jiang; Shengxuan Zhang; Chen Tan; Liqiong Peng; Ran Ding; Bing Tian; Xiaojie Song; Li Jiang (Pediatric Discovery)
ABSTRACT Epilepsy is a chronic neurological disorder characterized by abnormal synchronized neuronal discharges, leading to cognitive dysfunction. The ketogenic diet (KD) has shown promise as an effective treatment for drug‐resistant epilepsy (DRE), reducing seizures and improving cognitive and behavioral outcomes in patients. However, the precise neuroprotective mechanisms are not fully understood. This study aimed to investigate the effects of KD on cognitive impairment and hippocampal neurocircuit damage in rats with status epilepticus (SE), with a focus on a nuclear factor‐kappa B (NF‐κB) signaling. SE was induced using pilocarpine, and rats were assigned to KD and control groups. After 7 and 20 days of KD treatment, cognitive function was assessed using the elevated plus‐maze, Morris water maze, novel object recognition, and Y‐maze tests. Hippocampal tissue was analyzed for structural damage of neurocircuit. NF‐κB pathway activation was evaluated by western blot and immunofluorescence. Results indicated that KD significantly improved cognitive performance and reduced hippocampal damage. Additionally, KD inhibited NF‐κB pathway activation, evidenced by decreased levels of NF‐κB, p‐IκB, and proinflammatory cytokines. These findings suggest that KD may alleviate cognitive deficits and hippocampal damage by modulating the NF‐κB signaling, providing insights into its neuroprotective mechanisms and potential as an alternative treatment for epilepsy.